Lichen planus and metabolic syndrome: Is there a relation? - Rohit Singla; P K Ashwini; Betkerur Jayadev (Wolters Kluwer Medknow Publications, 2019)
Background: Recent data suggests association of lichen planus (LP) with various systemic disorders. Relationship between LP and metabolic syndrome (MS) is not yet taken into account. MS has been associated with increased risk of cardiovascular diseases. Hence, earlier detection and treatment could potentially decrease mortality and improve the quality of life in these patients. Objectives: To find out the association of LP with MS. Materials and Methods: About 100 LP patients and 50 healthy adults were investigated for fasting blood glucose (FBS) and lipid profile. MS was diagnosed as per National Cholesterol Education Program's Adult Treatment Panel III guidelines. Results: Serum cholesterol, triglycerides, low density lipoprotein (LDL-C), and very low density lipoprotein (VLDL-C) values were significantly increased in cases as compared to controls (P < 0.05 in all). About 42% of patients showed raised FBS level as compared to 10% controls (P = 0.0003). MS was more prevalent in cases than in controls (43% versus 26% respectively, P= 0.045). Odds ratio was highest in FBS and waist circumference. Limitations: As the cases and controls are included from a local area, the result may differ from other parts of the world. Conclusion: Diabetes mellitus, dyslipidemia, and MS are seen more commonly in LP patients.